Strengthening Business Sustainability at Al Kasyaf Foundation through the Development of an Innovative Entrepreneurship Model - Azwan Halim Shohibudu'a; Yunizar Yunizar (Politeknik Siber Cerdika Internasional, 2026)
Background: The sustainability of foundation-based social organizations faces challenges in business management, system integration, and adaptation to environmental changes. Objective: This study aims to analyze the actual conditions of multi-line management of social business in the Al Kasyaf Foundation, identify the dynamics of collaboration, innovation, as well as supporting and inhibiting factors for sustainability, as well as formulate innovative entrepreneurial models to strengthen organizational sustainability. Methods: The research uses a qualitative approach with a case study method. Data was obtained through in-depth interviews, observations, and documentation of the managers of the Al Kasyaf Foundation's business units, then analyzed using data reduction techniques, data presentation, and conclusion drawn. Results: The results show that inter-unit management is still informal with limited system integration, while collaboration and the implementation of the circular economy have developed organically. The main supporting factors include social capital based on religious values, resource integration, and external collaboration networks, while the main obstacles are limited human resources, weak management systems, dependence on a single source of income, and low digitalization. Conclusion: This research produces an innovative entrepreneurship model consisting of the integration of digital management systems, strengthening the circular economy, developing human resource capacity, and diversifying business units. The model is expected to be a strategy to strengthen economic, social, and environmental sustainability in community-based social organizations.